machine-learning/logistic_regression/binary.org
2021-02-21 10:07:19 +01:00

97 lines
6.3 KiB
Org Mode

#+TITLE: Binary Logistic Regression
#+AUTHOR: Loic Guegan
#+OPTIONS: toc:nil
#+LATEX_HEADER: \usepackage{fullpage}\usepackage{cancel}
#+latex_header: \hypersetup{colorlinks=true,linkcolor=blue}
Binary logistic regression are used to predict an binary issue (win/loss, true/false) according to
various parameters. First, we have to choose a polynomial function $h_w(x)$ according to the data
complexity (see \textit{data/binary\_logistic.csv}). In our case, we want to predict our issue (1
or 0) according to two parameters. Thus:
\begin{equation}
h_w(x_1,x_2) = w_1 + w_2x_1 + w_3x_2
\end{equation}
However, the function we are looking for should return a *binary* result! To achieve this goal, we
can use a sigmoid (or logistic) with the following property $\mathbb{R} \to ]0;1[$ with the following
form:
#+BEGIN_SRC python :results file :exports none :session
import numpy as np
import matplotlib.pyplot as plt
x=np.arange(-5,5,0.1)
plt.xlabel("X")
plt.ylabel("Y")
plt.title("Sigmoid Function")
plt.text(-3,0.5,r'$\frac{1}{1+e^{-x}}$',fontsize=30)
plt.plot(x,1/(1+np.exp(-x)))
plt.grid()
plt.savefig("sigmoid.png")
"sigmoid.png"
plt.close()
#+END_SRC
#+ATTR_LATEX: :width 10cm
[[file:sigmoid.png]]
To this end, we can define the following function:
\begin{equation}\label{eq:cost}
g_w(x_1,x_2) = \frac{1}{1+e^{-h_w(x_1,x_2)}}
\end{equation}
The next step is to define a cost function. A common approach in binary logistic function is to use
the *Cross-Entropy* loss function. It is much more convenient than the classical Mean Square Error
used in polynomial regression. Indeed, the gradient is stronger even for small error (see [[https://www.youtube.com/watch?v=gIx974WtVb4&t=110s][here]] for
more informations). Thus, it looks like the following:
\begin{equation}\label{eq:cost}
J(w) = -\frac{1}{n} \sum_{i=0}^n \left[y^{(i)}log(g_w(x_1^{(i)},x_2^{(i)})) + (1-y^{(i)})log(1-g_w(x_1^{(i)},x_2^{(i)}))\right]
\end{equation}
With $n$ the number of observations, $x_j^{(i)}$ is the value of the $j^{th}$ independant variable
associated with the observation $y^{(i)}$. The next step is to $min_w J(w)$ for each weight $w_i$
(performing the gradient decent, see [[https://towardsdatascience.com/gradient-descent-demystified-bc30b26e432a][here]]). Thus we compute each partial derivatives:
\begin{align*}
\frac{\partial J(w)}{\partial w_1}&=\frac{\partial J(w)}{\partial g_w(x_1,x_2)}\frac{\partial g_w(x_1,x_2)}{\partial h_w(x_1,x_2)}\frac{\partial h_w(x_1,x_2)}{\partial w_1}\nonumber\\
\frac{\partial J(w)}{\partial g_w(x_1,x_2)}&=-\frac{1}{n} \sum_{i=0}^n \left[y^{(i)}\frac{1}{g_w(x_1^{(i)},x_2^{(i)})} + (1-y^{(i)})\times\frac{1}{1-g_w(x_1^{(i)},x_2^{(i)})}\times (-1)\right]\nonumber\\
&=-\frac{1}{n} \sum_{i=0}^n \left[\frac{y^{(i)}}{g_w(x_1^{(i)},x_2^{(i)})} - \frac{1-y^{(i)}}{1-g_w(x_1^{(i)},x_2^{(i)})}\right]\nonumber\\
&=-\frac{1}{n} \sum_{i=0}^n \left[\frac{y^{(i)}(1-g_w(x_1^{(i)},x_2^{(i)}))}{g_w(x_1^{(i)},x_2^{(i)})(1-g_w(x_1^{(i)},x_2^{(i)}))} - \frac{g_w(x_1^{(i)},x_2^{(i)})(1-y^{(i)})}{g_w(x_1^{(i)},x_2^{(i)})(1-g_w(x_1^{(i)},x_2^{(i)}))}\right]\nonumber\\
&=-\frac{1}{n} \sum_{i=0}^n \left[\frac{y^{(i)}\cancel{-y^{(i)}g_w(x_1^{(i)},x_2^{(i)})} -g_w(x_1^{(i)},x_2^{(i)})\cancel{+y^{(i)}g_w(x_1^{(i)},x_2^{(i)})}}{g_w(x_1^{(i)},x_2^{(i)})(1-g_w(x_1^{(i)},x_2^{(i)}))}\right]\nonumber\\
&=\frac{1}{n} \sum_{i=0}^n \left[\frac{-y^{(i)} +g_w(x_1^{(i)},x_2^{(i)})}{g_w(x_1^{(i)},x_2^{(i)})(1-g_w(x_1^{(i)},x_2^{(i)}))}\right]\nonumber\\
\frac{\partial g_w(x_1,x_2)}{\partial h_w(x_1,x_2)}&=\frac{\partial (1+e^{-h_w(x_1,x_2)})^{-1}}{\partial h_w(x_1,x_2)}=-(1+e^{-h_w(x_1,x_2)})^{-2}\times \frac{\partial (1+e^{-h_w(x_1,x_2)})}{\partial h_w(x_1,x_2)}\nonumber\\
&=-(1+e^{-h_w(x_1,x_2)})^{-2}\times -e^{-h_w(x_1,x_2)}=\frac{e^{-h_w(x_1,x_2)}}{(1+e^{-h_w(x_1,x_2)})^2}\nonumber\\
&=\frac{e^{-h_w(x_1,x_2)}}{(1+e^{-h_w(x_1,x_2)})(1+e^{-h_w(x_1,x_2)})}=\frac{1}{(1+e^{-h_w(x_1,x_2)})}\frac{e^{-h_w(x_1,x_2)}}{(1+e^{-h_w(x_1,x_2)})}\nonumber\\
&=\frac{1}{(1+e^{-h_w(x_1,x_2)})}\frac{e^{-h_w(x_1,x_2)}+1-1}{(1+e^{-h_w(x_1,x_2)})}=\frac{1}{(1+e^{-h_w(x_1,x_2)})}\left(1+\frac{-1}{(1+e^{-h_w(x_1,x_2)})}\right)\nonumber\\
&=g_w(x_1,x_2)(1-g_w(x_1,x_2))\nonumber\\
\frac{\partial h_w(x_1,x_2)}{\partial w_1}=1\nonumber\\
\text{Finally:}\\
\frac{\partial J(w)}{\partial w_1}&=\frac{1}{n} \sum_{i=0}^n \left[\frac{-y^{(i)}+g_w(x_1^{(i)},x_2^{(i)})}{\cancel{g_w(x_1^{(i)},x_2^{(i)})(1-g_w(x_1^{(i)},x_2^{(i)}))}} \times \cancel{g_w(x_1^{(i)},x_2^{(i)})(1-g_w(x_1^{(i)},x_2^{(i)}))} \right]\nonumber\\
&=\frac{1}{n} \sum_{i=0}^n \left[-y^{(i)}+g_w(x_1^{(i)},x_2^{(i)})\right]
\end{align*}
\begin{align*}
\text{Similarly:}\\
\frac{\partial J(w)}{\partial w_2}&=\frac{1}{n} \sum_{i=0}^n x_1\left[-y^{(i)}+g_w(x_1^{(i)},x_2^{(i)})\right]\\
\frac{\partial J(w)}{\partial w_1}&=\frac{1}{n} \sum_{i=0}^n x_2\left[-y^{(i)}+g_w(x_1^{(i)},x_2^{(i)})\right]\\
\end{align*}
For more informations on binary logistic regression, here are usefull links:
- [[https://ml-cheatsheet.readthedocs.io/en/latest/logistic_regression.html][Logistic Regression -- ML Glossary documentation]]
- [[https://math.stackexchange.com/questions/2503428/derivative-of-binary-cross-entropy-why-are-my-signs-not-right][Derivative of the Binary Cross Entropy]]
* Desision Boundary
The method used here is similar to the one used [[https://scipython.com/blog/plotting-the-decision-boundary-of-a-logistic-regression-model/][here]]. In binary logistic regression, decision
boundary is located where:\\ \[g_w(x_1,x_2)=0.5 \implies h_w(x_1,x_2)=0\]
In addition we now that our decision boundary has the following form \[x_2=ax_1+b\]
Thus, we can easily deduce b since if $x_1=0$ we have $x_2=a\times 0 + b \implies x_2=b$. Thus:
\begin{equation}
h_w(0,x_2)=w_1 + w_3x_2=0\\
\implies x_2=\frac{-w_1}{w_3}
\end{equation}
To deduce the a coefficient, it is slighly more complicated. If we know two points $(x_1^a,x_2^a)$ and $(x_1^b,x_2^b)$
on the decision boundary line, we know that $a=\frac{x_2^b-x_2^a}{x_1^b-x_1^a}$. thus if we compute:
\begin{align*}
h_w(X_1^b,x_2^b)-h_w(X_1^a,x_2^a)&=\cancel{w_1}+w_2x_1^b+w_3x_2^b\cancel{-w_1}-w_2x_1^a-w_3x_2^a = 0 \\
&\implies w_2(x_1^b-x_1^a)+w_3(x_2^b-x_2^a) = 0 \implies \frac{w_2}{-w_3}=\frac{(x_1^b-x_1^a)}{(x_2^b-x_2^a)}=a
\end{align*}
Thus we have the decision boundary defined as follow:
\[ d(x) = \frac{w_2}{-w_3} x - \frac{w_1}{w_3} \]